Supercritical enhancement for separation of lauric acid and oleic acid in palm kernel oil (PKO) - Sarker, Md. Zaidul Islam; Nik Ab Rahman, Nik Norulaini; Omar, Anuar; Abdul Kadir, Mohd. Omar (Elsevier Inc., 2004)
The extraction of dehulled ground palm kernel using supercritical carbon dioxide (SC-CO2) as a solvent at a temperature of 80 ◦C and pressures ranging from 27.6 to 48.3 MPa was studied for 30–60 min. At 27.6, 34.5, 41.4 and 48.3 MPa the sample was extracted for 60, 40, 30 and 30 min, respectively, and the total oil achieved 37.5, 38.35, 41.0 and 44.75%, respectively. Within 30 min extraction at 27.6 MPa about 28.2% of oil was extracted and with increasing pressure, the extraction rate concurrently enhanced to 33.7, 41.0 and 44.75% at 34.5, 41.4, and 48.3 MPa, respectively. At 80 ◦C the solubility of the oil increased from about 4.01 to 14.11 g/100 g carbon dioxide as the pressure was increased from 27.6 to 48.3 MPa, however, maintaining constant temperature of 80 ◦C the solubility of oil increased with pressure. The extracted yield collected as about 1 g of oil in each fraction. The fatty acid composition of oil extracted varied with fractionation of the sample. Caprylic acid (C8), capric acid (C10), lauric acid (C12) and myristic acid (C14) were found to be decreased from the first to the last fraction (8th fraction). On the other hand there was an increase in palmitic (C16), stearic (C18:0), oleic (C18:1) and linoleic (C18:2) acids from first to the last fraction.